Urban ecology - Gaston, Kevin J.; Barton, Jo; Bates, Adam; Boone, Christopher; Davies, Zoe G.; Edmondson, Jill L.; Evans, Karl L.; Fuller, Richard A.; Hale, James; Harlan, Sharon L.; Irvine, Katherine N.; James, Philip; et al. (Cambridge ; New York : Cambridge University Press, 2010)
"This is the urban century in which, for the first time, the majority of people live in towns and cities. Understanding how people influence, and are influenced by, the 'green' component of these environments is therefore of enormous significance. Providing an overview of the essentials of urban ecology, the book begins by covering the vital background concepts of the urbanisation process and the effect that it can have on ecosystem functions and services. Later sections are devoted to examining how species respond to urbanisation, the many facets of human-ecology interactions, and the issues surrounding urban planning and the provision of urban green spaces. Drawing on examples from urban settlements around the world, it highlights the progress to date in this burgeoning field, as well as the challenges that lie ahead"--
Machine generated contents note: List of contributors; Preface; Acknowledgements; 1. Urban ecology Kevin J. Gaston; 2. Urbanisation Kevin J. Gaston; 3. Urban environments and ecosystem functions Kevin J. Gaston, Zoe G. Davies and Jill L. Edmondson; 4. Individual species and urbanisation Karl L. Evans; 5. Species diversity and urbanisation: patterns, drivers and implications Gary W. Luck and Lisa T. Smallbone; 6. Urbanisation and alien invasion Stefan Klotz and Ingolf Kühn; 7. Interactions between people and nature in urban environments Richard A. Fuller and Katherine N. Irvine; 8. Urban ecology and human social organisation Paige S. Warren, Sharon Harlan, Christopher Boone, Susannah B. Lerman, Eyal Shochat and Ann P. Kinzig; 9. Urban ecology and human health and wellbeing Jo Barton and Jules Pretty; 10. Bringing cities alive: the importance of urban greenspaces for people and biodiversity Jon Sadler, Adam Bates, James Hale and Philip James; 11. Integrating nature values in urban planning and design Robbert Snep and Paul Opdam; 12. Urban futures Michael L. McKinney; Index.
Bibliografija
Kazalo
Keywords: urbana ekologija (Sociologija); planiranje grada -- ekonomski aspekt; održivi razvoj